1997
DOI: 10.1111/j.1471-0528.1997.tb11009.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metronidazole therapy on preterm birth in women with bacterial vaginosis flora (Gardnerella vaginalis): a randomised, placebo controlled trial

Abstract: Objective To ascertain whether metronidazole treatment of women with a heavy growth of Gardnerella Design A multicentre, randomised, placebo-controlled trial Setting Four metropolitan hospitals.Participants Eight hundred and seventy-nine singleton women with a heavy growth of G. vaginalis or Interventions Oral metronidazole (400 mg) or placebo twice daily for two days at 24 weeks of gestation, Main outcome measures Spontaneous preterm birth less than 37 weeks.Results Intention-to-treat analysis showed no diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
2
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(186 citation statements)
references
References 27 publications
4
171
2
4
Order By: Relevance
“…These researchers recommended the longer course of therapy to eradicate upper genital tract organisms 11 . The results of this study supported those of McDonald et al 10 in that metronidazole did not reduce preterm delivery among the general population of pregnant women, nor did it reduce hospital admissions for preterm labor or preterm premature rupture of the membranes, postpartum endometritis, clinical intra-amniotic infections, vaginal infections serious enough to require treatment, and treatment with tocolytic drugs. The placebo and metronidazole groups did not differ with regard to incidence of admissions to the neonatal intensive-care unit, passage of meconium, or fetal death/neonatal death.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…These researchers recommended the longer course of therapy to eradicate upper genital tract organisms 11 . The results of this study supported those of McDonald et al 10 in that metronidazole did not reduce preterm delivery among the general population of pregnant women, nor did it reduce hospital admissions for preterm labor or preterm premature rupture of the membranes, postpartum endometritis, clinical intra-amniotic infections, vaginal infections serious enough to require treatment, and treatment with tocolytic drugs. The placebo and metronidazole groups did not differ with regard to incidence of admissions to the neonatal intensive-care unit, passage of meconium, or fetal death/neonatal death.…”
supporting
confidence: 80%
“…However, since the clinical diagnosis of BV need not be symptomatic, screening all pregnant women who have risk factors may be unnecessary and not cost-effective 21 , while the most advantageous time to screen and the optimum dosage of antibiotic is uncertain. 7 Morales et al 9 McGregor et al 1 McDonald et al 10 Cochrane database 3 Joesoef et al 12 Carey et al…”
Section: Discussionmentioning
confidence: 99%
“…• Antibiotic treatment for women with a prior preterm birth and bacterial vaginosis has been suggested in secondary analyses to reduce the risk of recurrent preterm birth, 97,98 but evidence is inconsistent. [12][13][14]99,100 Antibiotic treatment of women with a prior preterm birth and a positive fetal fibronectin test 10 and interconceptional antibiotics given to women with a prior preterm birth 11 were both associated with an increased rate of recurrent preterm birth.…”
Section: Interventions Suggested To Reduce the Risk Of Recurrent Pretmentioning
confidence: 99%
“…There was no benefit from treatment in women who did not have BV. A large Australian study showed a small non-significant trend for a benefit of using short course metronidazole 400 mg bd for 2 days, repeated after 1 month if BV was still present [42]. Subgroup analysis showed a reduction in preterm birth in the treatment group, particularly those with a prior preterm birth who adhered to the medication.…”
Section: Treatment In Pregnancymentioning
confidence: 97%